CCR4 and CCR5 Involvement in Monocyte-Derived Macrophage Migration in Neuroinflammation - Kim, Jong Youl; Kim, Jiwon; Huang, Meiying; Kosonen, Renée; Lee, Jong Eun (Frontiers in Immunology, 2022)
Microglia, resident macrophages in the brain, play major roles in neuroinflammation after an acute ischemic stroke. Our recent animal stroke model showed that interleukin (IL)-4 and IL-13 released by microglia are converted into monocyte-derived macrophages. However, the correlation with the migration mechanism of these cells is still unclear. This study aimed to clarify the effect of these cells on their migration and to identify potential targets that influence neuroinflammatory conditions. Inflammatory conditions were induced by lipopolysaccharide (LPS) treatment in in vitro and in vivo models. Cell migration was observed using transwell assay, and target chemokines were screened using the proteome profiler array in the in vitro model. Intravital, IVIS, and CLARITY imaging were used in the in vivo model. After LPS (1 ng/ml) treatment in BV2 (microglia cell line) and J774 (monocyte/macrophage cell line) cells, BV2 migration was approximately two-fold more enhanced compared to J774 migration. Overall, six types of chemokine C-C motif ligands (CCLs) were detected from the BV2 conditioned medium with LPS. These CCLs were related to C-C motif receptor (CCR)4 and CCR5. In the in vivo model, CCR4 and CCR5 antagonist significantly inhibited the migration of monocyte-derived macrophages to brain tissue following LPS (5 µg) treatment. In conclusion, the chemokines released by microglia may influence migration of monocyte-derived macrophages in post-ischemic stroke neuroinflammation. CCR4 and CCR5 expressed on monocyte-derived macrophages interacted with these chemokines and induced migration. Therefore, CCR4 and CCR5 may be explored as new therapeutic targets for neuroinflammation.